5G New Radio: Dynamic Time Division Duplex Radio Resource Management Approaches - Samidi F.S.; Radzi N.A.M.; Ahmad W.S.H.M.W.; Abdullah F.; Jamaludin M.Z.; Ismail A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Antennas; Energy efficiency; Machine learning; Natural resources management; Network function virtualization; Radio communication; Radio transmission; Resource allocation; Time division multiplexing; Exponential increase; Interference management; Machine learning methods; Radio resource management; Resource management schemes; Rule based algorithms; Time division duplex; Transmission power; 5G mobile communication systems